Student perceptions of a primary education degree and its impact on the development of their professional skills - Mercedes Cuevas López; Francisco Díaz Rosas (Arizona State University, 2019)
This study, an analysis of the specific skills acquired through the primary education degree, was carried out at one of the University of Granada's faculties offering this degree. This work reviewed the teaching guides of curriculum subjects to check the skills intended to be acquired from them. Subsequently, Student opinions of the faculties of education, economics and technology in Ceuta was collected to determine to what extent the students perceive having acquired these skills. The sample consists of 105 students in different stages of the degree. The results obtained show an acceptable level of skills acquired, and at the same time, the existence of certain training deficiencies. The authors conclude it is advisable to extend the study to other faculties of the University of Granada to determine whether the educational deficiencies affect the design of the degree.